What is the system of monument protection? Unanswered questions ... - Gawlicki, Marcin (Protection of Cultural Heritage, 2016)
The Act of 23 July 2003 on the Protection and Guardianship of Monuments has never been flawless and the historic preservation milieu has been aware of the consequently deteriorating monument protection system. This article explores the following problems existing in the area of cultural heritage: description and evaluation of cultural heritage, document production rules, sources of financing works carried out to heritage, effectiveness of legal processes, professional development of members of staff, organisational structure of historic preservation offices, and cooperation opportunities on different levels of state and local government administration bodies dealing with protection of monuments and sites. While reading questions provided in this article, one may be willing to ponder on directions of expected changes and ways of introducing them in Poland.